Kehancuran Benda Cagar Budaya Saat Konflik Bersenjata: Eksistensi Blue Shield Emblem - Mokhamad Gisa Vitrana; Anna Anindita Nur Pustika (Faculty of Law, Maranatha Christian University, 2023)
The intentional destruction of cultural heritage in armed conflict that is not used for military purposes causes the greatest losses of mankind. Lots of cultural properties have great value as the cultural heritage of mankind. Creating the distinctive emblem through the 1954 Hague Convention and its two Protocols d become a crucial way in terms of the protection of cultural properties. Based on these instruments, three categories of distinctive emblem gave for cultural properties over general, special and enhanced protection. It could impact cultural property under unnecessary damage when armed conflict occurred. Therefore, this research d a crucial basic issue on how form, function, and assignation of the distinctive emblem should be, based on the provisions of the 1954 Hague Convention and its two Protocols, as well as related International Humanitarian Law. As the result of this research, it can be said that the existence of a distinctive emblem is remained unclear in terms of its size form and assignation on cultural property. This research ed that the use of distinctive emblem shall be regulated by decisive provisions through a Convention or such a guideline of implementation so that distinctive emblem can be seen by the dispute parties to avoid unnecessary damage to cultural property.